Word Formation on Social Media - Weni Prasita; Antari, Risky; Nurkhalizah, Nurkhalizah; Damanik, Emeliya Sukma Dara (Indonesian Gender and Society Journal, 2022)
The word is the smallest part in language that can be spoken or written which is the embodiment of thoughts used in language. There are several processes in the formation of words and are divided into several types in their formation). The research aims to analyze word-formation processes on social media. This research used a qualitative method that expanded the research by observing events and phenomena happening around us. This research also collects data by observing the incident that happens across social media in general. Analysis carried out based on materials related to semantic theory.  The results obtained from this research are that there are several examples of each word formation process, two examples for borrowing, two examples for coinage, two examples for compounding, two examples for acronyms, one example for blending, two examples for clipping, and no examples for back formation were found and conversion too, as well as two examples for inflection and two examples for derivation.